2015
DOI: 10.1055/s-0034-1393124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additional surgery after noncurative endoscopic submucosal dissection for early gastric cancer

Abstract: Background and study aims: Endoscopic submucosal dissection (ESD) is a standard treatment for early gastric cancer (EGC) without lymph node metastasis. However, some patients undergo noncurative ESD. The aim of the present study was to assess the long-term clinical outcomes of noncurative ESD with or without additional surgery. Patients and methods: We investigated the chart data from all patients who had undergone ESD for EGC at Saga Medical School Hospital and Saga Prefectural Medical Centre Koseikan betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 24 publications
(12 reference statements)
5
38
0
Order By: Relevance
“…This study demonstrated that OS and disease-free survival did not differ significantly between patients treated with additional surgical resection and patients undergoing simple follow-up after ESD. More recently, Yamanouchi et al [21] reported that the DSS rate did not differ significantly between observation and additional surgery groups after noncurative ESD, although there were only 79 noncurative gastric ESD patients in their report. In addition, Hoteya et al [22] described that gastric-cancer-related deaths and OS rates did not differ significantly between observation and additional surgery groups; however the number of noncurative gastric ESD patients included in this study was also less than 200 (165 patients).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This study demonstrated that OS and disease-free survival did not differ significantly between patients treated with additional surgical resection and patients undergoing simple follow-up after ESD. More recently, Yamanouchi et al [21] reported that the DSS rate did not differ significantly between observation and additional surgery groups after noncurative ESD, although there were only 79 noncurative gastric ESD patients in their report. In addition, Hoteya et al [22] described that gastric-cancer-related deaths and OS rates did not differ significantly between observation and additional surgery groups; however the number of noncurative gastric ESD patients included in this study was also less than 200 (165 patients).…”
Section: Discussionmentioning
confidence: 82%
“…Although several studies have described the clinical outcomes of noncurative gastric ER patients, the definition of noncurative gastric ER differs between studies; most of these studies have assessed the clinical outcomes of noncurative gastric ER patients in small numbers of patients without detailed statistical analysis [15][16][17][18][19][20][21][22][23][24][25]. For example, noncurative gastric ER was defined according to the Japanese gastric cancer treatment guidelines in some studies but was defined according to the original criteria in others [4,[15][16][17][18][19][20][21][22][23][24][25]. In addition, with the exception of two studies by Oda et al [15] and Yang et al [16], fewer than 200 noncurative gastric ER cases were included in previous studies [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite improvements in gastrointestinal endoscopy and surgery, the prognoses of advanced gastric cancer patients remain poor, with a 5-year survival percentage of < 30% [20][21][22]. Studies of the molecular mechanisms involved in different stages of gastric cancer are urgently needed for the development of better methods of diagnoses and improvements in therapeutic treatments for this disorder.…”
Section: Discussionmentioning
confidence: 99%